Multiple loci associated with indices of renal function and chronic kidney disease. - Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Hwang, Shih-Jen; Katz, Ronit; Li, Man; Yang, Qiong; Gudnason, Vilmundur; Launer, Lenore J; Harris, Tamara B; Smith, Albert V; Arking, Dan E; et al. (Nat Genet, 2009)
Chronic kidney disease (CKD) has a heritable component and is an important global public health problem because of its high prevalence and morbidity. We conducted genome-wide association studies (GWAS) to identify susceptibility loci for glomerular filtration rate, estimated by serum creatinine (eGFRcrea) and cystatin C (eGFRcys), and CKD (eGFRcrea < 60 ml/min/1.73 m(2)) in European-ancestry participants of four population-based cohorts (ARIC, CHS, FHS, RS; n = 19,877; 2,388 CKD cases), and tested for replication in 21,466 participants (1,932 CKD cases). We identified significant SNP associations (P < 5 × 10(-8)) with CKD at the UMOD locus, with eGFRcrea at UMOD, SHROOM3 and GATM-SPATA5L1, and with eGFRcys at CST and STC1. UMOD encodes the most common protein in human urine, Tamm-Horsfall protein, and rare mutations in UMOD cause mendelian forms of kidney disease. Our findings provide new insights into CKD pathogenesis and underscore the importance of common genetic variants influencing renal function and disease.
Keywords: Chromosome Mapping; Cohort Studies; Genetic Variation; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Meta-Analysis as Topic; Mucoproteins; Netherlands; Polymorphism, Single Nucleotide; Prevalence; Uromodulin